Identification of a PCSK9-LDLR disruptor peptide with in vivo function. Issue 2 (17th February 2022) - Brousseau, Margaret E.; Clairmont, Kevin B.; Spraggon, Glen; Flyer, Alec N.; Golosov, Andrei A.; Grosche, Philipp; Amin, Jakal; Andre, Jerome; Burdick, Debra; Caplan, Shari; Chen, Guanjing; Chopra, Raj; et al.
Summary: Proprotein convertase subtilisin/kexin type 9 (PCSK9) regulates plasma low-density lipoprotein cholesterol (LDL-C) levels by promoting hepatic LDL receptor (LDLR) degradation. Therapeutic antibodies that disrupt PCSK9-LDLR binding reduce LDL-C concentrations and cardiovascular disease risk. The epidermal growth factor precursor homology domain A (EGF-A) of the LDLR serves as a primary contact with PCSK9 via a flat interface, presenting a challenge for identifying small molecule PCSK9-LDLR disruptors. We employ an affinity-based screen of 10 13 in vitro -translated macrocyclic peptides to identify high-affinity PCSK9 ligands that utilize a unique, induced-fit pocket and partially disrupt the PCSK9-LDLR interaction. Structure-based design led to molecules with enhanced function and pharmacokinetic properties (e.g., 13 PCSK9i ). In mice, 13 PCSK9i reduces plasma cholesterol levels and increases hepatic LDLR density in a dose-dependent manner. 13 PCSK9i functions by a unique, allosteric mechanism and is the smallest molecule identified to date with in vivo PCSK9-LDLR disruptor function. Graphical abstract: Highlights: Discovery of PCSK9 ligands that utilize a unique, induced-fit pocket A nonbiologic agent capable of disrupting the PCSK9-LDLR interaction in vivo Abstract : Brousseau et al. have identified macrocyclic peptides that bind PCSK9 with low-nanomolar affinity, disrupt PCSK9 function, and utilize an induced-fit pocket. 13 PCSK9i functions by a distinct, allosteric mechanism and is the smallest molecule identified to date with in vivo PCSK9-LDLR disruptor function.